A CROSS-SECTIONAL STUDY TO ASSESS THE PATTERN OF SELF-MEDICATION USED FOR DIARRHEA AMONG MEDICAL STUDENTS IN TERTIARY CARE TEACHING HOSPITAL OF CENTRAL INDIA - MISHRA, POOJA SOLANKI; TIWARI, ASHUTOSH; SHINDE, MEGHNA; RASTOGI, DEEPTI; KHARAT, AVINA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study is to assess the drug usage pattern, personal hygiene, and sanitation practices among day scholars and hosteller medical students. Methods: A questionnaire-based cross-sectional study was conducted at MGM Medical College and M.Y. Hospital, Indore. Undergraduate and postgraduate medical students who experienced episodes of diarrhea in the past 6 months were included in the study. Diarrhea occurring due to organic causes was excluded. Data were collected using a Google or physical form and were analyzed using descriptive statistics. Results: 254 students who suffered from diarrhea in the past 6 months participated in the study, out of which 56% were hostellers. Commonly used drugs were ofloxacin, metronidazole, etc. 50.2% of them took self-medication; the majority of them were hostellers. Students were found to eat outside at least once a week. Personal hygiene and sanitation were more compromised among hostellers than day scholars. Conclusion: Personal hygiene and sanitation practices should be improved among medical students, especially hostel students. These students, despite being from medical backgrounds, still take irrational medication. Therefore, there is a need for increased awareness regarding drug usage, and self-medication should be discouraged.